2020
DOI: 10.1155/2020/5068268
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analysis of Laparoscopic Surgery Combined with Wuda Granule to Promote Rapid Recovery of Patients with Colorectal Cancer Using UPLC/Q‐TOF‐MS/MS

Abstract: Surgery is the primary curative treatment for patients with nonmetastasized colorectal cancer (CRC). Rate of complications, morbidity, mortality, and overall survival of patients with CRC are factors associated with speed of recovery following surgery. Wuda granule (WD) is a traditional Chinese medicine (TCM) prescription used to promote rapid recovery after surgery. However, the specific mechanism of action of WD has not been characterized. Our study included 60 patients with clear histopathological evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Metabonomics has been used to study the organism as a whole, which is consistent with the holistic view of TCM and the concept of syndrome differentiation and treatment ( Wang et al, 2017 ). Because the modernization of TCM is becoming necessary and urgent ( Li et al, 2008 ), metabolomics represents a modern technology with a great potential toward understanding the efficacy and mechanism of TCM ( Sun et al, 2012 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabonomics has been used to study the organism as a whole, which is consistent with the holistic view of TCM and the concept of syndrome differentiation and treatment ( Wang et al, 2017 ). Because the modernization of TCM is becoming necessary and urgent ( Li et al, 2008 ), metabolomics represents a modern technology with a great potential toward understanding the efficacy and mechanism of TCM ( Sun et al, 2012 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 58 ]. In the authors’ previous works [ 14 ], they conducted a network analysis of the targets of AGIs from SBG and that of commercial drugs for T2D. The interaction data were also calculated by the STRING database.…”
Section: Discussionmentioning
confidence: 99%
“…In the authors’ previous studies [ 14 ], 13 α‐glucosidase inhibitors (AGIs) were identified from SBG by ultrafiltration LC‐MS method, including tenaxin I, skullcapflavone II, viscidulin III, etc. Detailed information about these compounds is listed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolisms (or metabonomics) is a discipline that developed after proteomics and genomics ( 15 ). It observes the dynamic changes of metabolites before and after the biological system is stimulated or disturbed, and uses various analytical tools to obtain the metabolic network of the biological system ( 16 ).…”
mentioning
confidence: 99%